Liderazgo gerencial y desempeño del personal administrativo de la Municipalidad Distrital de Guadalupe – 2022 - Alquizar Espinoza, Geniffet Liseth (2022)
The main objective of this investigation was to determine the relationship between "managerial leadership" and the administrative "performance of personnel" of the District Municipality of Guadalupe - 2022. Addressing the following research problem: How are managerial leadership and the performance of the administrative staff of the District Municipality of Guadalupe - 2022?, was established as a hypothesis: managerial leadership is positively related to the performance of the administrative staff of the District Municipality of Guadalupe - 2022. The methodology used was of a applied, quantitative, descriptive - correlational and transversal. With a population of 83 workers: 64 subordinate workers and 19 managerial workers, applying a non-probabilistic sampling for convenience, establishing an inclusion and exclusion criteria, which only included the 64 subordinate workers of the Guadalupe District Municipality. The data collection instrument was the questionnaire which was ordinal using a Likert scale for the questions. Concluding that the relationship between managerial leadership and the performance of the administrative staff of the District Municipality of Guadalupe - 2022 is 0.519 according to Spearman's Rho coefficient, which classifies it as a medium positive correlation. Being able to delimit, that, when there is a good managerial leadership, the performance of the collaborators would increase due to the existence of a positive correlation, in the same way to the inverse when a bad managerial leadership is developed, this has repercussions by correlation in a bad performance of the administrative personnel.